THE REPRESENTATION OF THE CONFLICT BETWEEN FPI AND AKKBB REGARDING THE MONAS INCIDENT (A CDA STUDY OF TWO HEADLINES OF KOMPAS AND REPUBLIKA) - Khoiri Jinan, - (2008)
This study investigates the representation of the Monas Incident in Kompas and Republika. The paper elaborates two major problems. First, it examines how the conflict is represented. Second, it explores the ideology behind the representation. It employs Critical Discourse Analysis (CDA) as the framework for the discussion. The data were taken from Kompas and Republika. In conducting the analysis, the present study relies on Van Dijk's analytical framework (Socio-cognitive CDA). It included the macrostructure, superstructure, and microstructure analyses. The results show that there are differences between Kompas and Republika in representing the conflict. Kompas tends to put FPI as a negative party. On the other hand, Republika tends to put the blame on government and AKKBB. This was investigated through thematization, schematization, transitivity, and lexicalization. Based on the result, it is concluded that Kompas and Republika have different ideologies. Hence, they represent one event in different ways.